The Influence of Family Support on Rumination in Job Seekers in Padang City - DEWI, RINDU PERMATA; RIZAL, RIZAL KURNIAWAN (Causalita, 2024)
The world of work is the target of all job seekers or job seekers. With the increasing number of job seekers, the higher the unemployment rate. This research aims to find out how family support influences rumination among job seekers in Padang City. This research uses a quantitative approach. The research sample consisted of 149 job seekers who were selected using non-probability sampling techniques with purposive sampling type. Data collection uses a Likert scale which consists of two scales, namely the family support scale adopted from Febrina (2021) and modified by researchers and the rumination scale adopted from Dharmawan (2023). Data analysis uses simple linear regression techniques. The results of the research show that (1) the level of rumination among job seekers in Padang City is generally in the high categorization, (2) the level of family support for job seekers in Padang City is generally in the medium categorization, (3) there is a positive and significant influence between family support against rumination among job seekers in Padang City with a contribution value of 18.5%.